Pengaruh Kualitas Sumber Daya Manusia, Sarana Pendukung Dan Komitmen Pimpinan Terhadap Kinerja Satuan Kerja Perangkat Daerah (SKPD) Dalam Penyusunan Laporan Keuangan Skpd Di Lingkungan Pemerintah Provinsi Sulawesi Utara - Pandey, Brammy (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2014)
This study on the effect of human resources, means of support and commitment to the performance of work units (SKPD) in the preparation of financial statements in the North Sulawesi provincial government, such research is still relatively small, and the results of the study are still varied and inconsistent. The purpose of this research was conducted to find whether there is empirical evidence Effects of human resources, means of support and commitment to performance on education in the preparation of financial statements in Sulawesi Utara.Populasi this study are all available on education in the government of North Sulawesi province. The unit of analysis is the head of the organizational work units. Data was collected through questionnaires delivered directly by the author. Before testing the hypothesis with multiple regression analysis, prior testing and test data quality classical assumptions. The results showed that the partial human resources, means of support and commitment to influence performance on education.